2006
DOI: 10.1111/j.1471-8286.2006.01384.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of microsatellite markers in the tiger mosquito Aedes albopictus (Skuse)

Abstract: Among the numerous molecular markers available in population genetics, microsatellites are one of the most powerful tools developed in recent years. This paper describes the isolation of six polymorphic microsatellite loci in the tiger mosquito Aedes albopictus using an enriched genomic library technique. Such loci should be an efficient tool in population genetic studies for this mosquito species

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 7 publications
0
28
0
Order By: Relevance
“…albopictus [26], one (AealbB52, Table 2) was not variable and the genetic resolution obtained using the remaining five markers was not considered adequate. We screened some Ae.…”
Section: Methodsmentioning
confidence: 99%
“…albopictus [26], one (AealbB52, Table 2) was not variable and the genetic resolution obtained using the remaining five markers was not considered adequate. We screened some Ae.…”
Section: Methodsmentioning
confidence: 99%
“…For mosquitoes, six SSRs were isolated in Ae. albopictus using an enriched genomic library technique (Porretta et al, 2006), and 20, 21 and 13 SSRs were identified in An. minimus, An.…”
Section: Ssr Numbers In 23 Mosquito Species Genomesmentioning
confidence: 99%
“…dirus (Bonizzoni et al ., ), An. maculatus (Rongnoparut et al ., ) and Aedes albopictus (Porretta et al ., ). The SSRs of An.…”
Section: Introductionmentioning
confidence: 99%
“…Although the previous studies provided important insights into the possible origin of the invasions, their results were sometimes contradictory [e.g., the case of Greece (Kamgang et al, 2011;Manni et al, 2017) or Brazil (Birungi & Munstermann, 2002;Kambhampati, Black, & Rai, 1991)]. However, determining the origin of the invasions unequivocally and/or at a high level of resolution would be valuable for a variety of public health interventions (Beebe et al, 2013;Delatte et al, 2013;Galtier, Nabholz, Glemin, & Hurst, 2009;Goubert, Minard, Vieira, & Boulesteix, 2016;Hurst & Jiggins, 2005;Manni et al, 2015;Medley, Jenkins, & Hoffman, 2015;Mousson et al, 2005;Porretta, Gargani, Bellini, Calvitti, & Urbanelli, 2006;Zhong et al, 2013). First, knowledge regarding the source of an introduction's origin(s) can provide information on the invasive population's likely mode of transportation (Goubert et al, 2016;Jackson et al, 2015;Powell & Tabachnick, 2013).…”
mentioning
confidence: 99%